Persyaratan Khusus Dalam Ragam Akad Syirkah Pada Literatur Fikih Mazhab - Ratu Humaemah (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2019)
Adjustment of the application of syirkah in sharia banking goes straight with regard to the Quran, Sunnah, fikih school in order to formulate the objectives of Islamic law in it. This is a research on historical literature and fiqh norms about special requirements in a variety of existing syirkah covenants. The understanding of language from syirkah is still permeated by various meanings in the four fiqh school. Both have the same pressure on the existence of mixing assets and contracts. two categories of forms, namely: Syirkah al-Amlak (alliance due to ownership) and Syirkah al-’uqūd (alliance due to a contract). The requirements in each form of syirkah contract are not merely those that always exist in the general understanding of syirkah. Each form can have special requirements tailored to the situations and conditions that support the willingness of each party in the Syirkah contract.